2022
DOI: 10.1093/advances/nmac097
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Lipid Profiles around the World: A Systematic Review and Meta-Analysis

Abstract: Reported breast milk lipid concentrations may vary with geographical region, postnatal age and year of sample collection. In this review, we summarized data on the concentrations of total fat, total phospholipids, cholesterol and fatty acids in human milk worldwide and their variation according to lactation stage, study area and sample collection year. A systematic literature search was performed using the PubMed, Embase, Web of Science and Medline databases for English language papers and Wanfang and China Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 207 publications
0
12
0
Order By: Relevance
“…In parallel to other cohorts, SFA relative levels were also higher in our cohort and PUFAs, LA, ARA, Omega-3, and ALA were lower, compared to these Chinese women. Indeed, an important recent review including 186 different HM studies showed that HM from Western countries had significantly higher concentrations of MUFAs and lower concentrations of PUFAs, total Omega-6 PUFA, compared with those from non-Western countries ( 89 ). In this review median SFA relative levels are also lower, and median PUFA relative levels were also higher than in our cohort of Central-African women.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to other cohorts, SFA relative levels were also higher in our cohort and PUFAs, LA, ARA, Omega-3, and ALA were lower, compared to these Chinese women. Indeed, an important recent review including 186 different HM studies showed that HM from Western countries had significantly higher concentrations of MUFAs and lower concentrations of PUFAs, total Omega-6 PUFA, compared with those from non-Western countries ( 89 ). In this review median SFA relative levels are also lower, and median PUFA relative levels were also higher than in our cohort of Central-African women.…”
Section: Discussionmentioning
confidence: 99%
“…ARA and DHA are present in human milk, albeit in much lower amounts than their precursors. The wide variation in DHA content is largely due to maternal consumption of seafood [3 ▪ ]. Whether the breast milk of premature babies contains higher levels of DHA is controversial, as a recent study contradicts previous ones [9].…”
Section: Estimates Of the Need For Long Chain-polyunsaturated Fatty A...mentioning
confidence: 93%
“…Other possible outcomes such as retinopathy of prematurity (ROP) and bronchopulmonary dysplasia (BPD) may also be influenced by these fatty acids due to their role as mediators of inflammation and/or oxidative stress [1,2]. However, determining the appropriate intake of LC-PUFA in infants is difficult because the levels of these fatty acids in breast milk vary [3 ▪ ,4 ▪ ,5] and they can also be synthesized endogenously. In preterm infants, this is even more difficult, as requirements are mainly estimated based on the fetal accretion rates, which remain largely uncertain…”
Section: Introductionmentioning
confidence: 99%
“…These tri-layer structures deliver triacylglycerols, phospholipids, gangliosides, and many other lipid classes, to the infant [ 13 ]. The lipid portion of human milk is relatively complex, with wide intra- and inter-individual variation [ 14 ]. Although frequently thought to originate directly from maternal diet, the link between human milk lipids and diet is complex, with diet alone unable to account for the entire milk lipidome.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this review is to present the existing evidence on the origins of human milk lipids and small metabolites to inform future research directions and application. A high degree of variability in lipid and small metabolite concentrations has been identified across milk samples from different individuals around the globe [ 14 , 34 ], suggesting that determination of milk composition is complex and dynamic. Human milk lipids and small metabolites may be synthesized locally within the mammary gland (by the mammary cells or the milk microbiota) or they may be incorporated from maternal circulation (originating from the maternal diet, maternal gut microbiota, or other non-mammary tissue) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%